The Role of New Media towards the Way K-Pop Fans Do Fashion as Their Self Representation - Sihombing, Lambok Hermanto (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
Korean pop (K-pop) culture has become a global phenomenon, significantly influencing youth lifestyles and fashion trends, especially in countries like Indonesia. This study investigates how new media acts as a central platform through which K-pop fans engage with and adopt fashion styles inspired by idols, and how these styles are used for identity construction and self-representation. The research focuses on Indonesian youth aged 15–25 who actively follow BTS, EXO, and Blackpink, the groups with the largest and most engaged fandoms in the country. Using questionnaires and visual documentation from social media, this study draws on theories of new media, fandom, and self-representation. The findings reveal that new media platforms not only disseminate K-pop fashion trends but also empower fans to creatively express their social identity and sense of belonging through personalized fashion choices aligned with their fandom.